ANALISIS STRATEGI MANAJEMEN PELATIHAN DAN PENGEMBANGAN KARYAWAN UNTUK MENINGKATKAN KINERJA ORGANISASI PADA PT SEMEN TONASA DI KABUPATEN PANGKEP - Hasanuddin, Arnas; Iskandar, Muh. Rezky; Risman, Risman (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the influence of Employee Training and Development Management on Organizational Performance at PT Semen Tonasa in Pangkep Regency, both partially and simultaneously. The background of this study is the importance of an effective human resource strategy to support organizational performance achievement in facing increasingly fierce competition in the cement industry. This type of research is quantitative with a multiple linear regression analysis approach. The results of the study indicate that partially, Employee Training and Development Management has a positive but insignificant effect on Organizational Performance. Simultaneously, both variables also have no significant effect on organizational performance with a contribution of 11.3% (R² = 0.113), while the remaining 88.7% is influenced by other factors outside this study, such as leadership, work culture, technology utilization, and employee motivation. These findings indicate that employee training and development programs need to be directed more strategically and measurably in order to have a real impact on improving organizational performance.